Passive Defence in Tehran: An Evaluation of Legal Frameworks - Vahide Ebrahimnia; Mehrdad Ghaedi (صفه, 2020)
Iran's strategic location in the Middle East, the continual threats by foreign countries, and the breaking out of numerous wars in its neighbouring countries, have necessitated the planning for urban spatial arrangements in order to deal with war crises. This is addressed in the Supreme Leader’s policies, the ‎‘Formation of the Passive Defence Organisation’ bill, as well as other regulations. This paper focuses on a key element of passive defence, namely, an integrated legal structure for preventive measures in Tehran’s spatial planning. Home to over 1500 official institutions, from political to military and diplomatic, the question is about the degree to which the present legal structures are capable of supporting the city’s passive defence, and the opportunities and obstacles on the way.   To answer this question, the Delphi method has been employed to analyse subjective factors, and document and text analysis methods for objective ones. The findings of the paper shows that territorial comprehensiveness, legal dogmatism , clarity of the language, accessibility, and achieving sufficient spatial requirements generate opportunities, whilst the lack of implementation guarantees, thematic comprehensiveness, people in charge, necessary details, overlaps and conflicts, along with the openness of laws to interpretations are among treats. Furthermore, although responsible authorities are formally named, the multiplicity of institutions and their conflicts of remit, as well as their weakness in establishing horizontal lines of communication diminish both the influence and efficiency of their decision- and policy-making.‎